Morphology and multigene phylogeny reveal a new species of Lindtneria (Agaricales, Basidiomycota) from South China - Guan, Qianxin; Dong, Jiahui; Chu, Wanshan; Wu, Fang; Zhang, Lirong (Phytotaxa, 2025)
During a survey of macrofungi in Anhui Province, China, two interesting specimens of Lindtneria were collected; based on morphology and multigene phylogenetic analysis, the two specimens are described as a new species, L. terrestris. The species is characterized by poroid basidiomata with irregular pores, buff-yellow to light-yellow pore surface when fresh, a monomitic hyphal system having septate generative hyphae with or without clamp connections, cylindrical to subclavate basidia frequently with cyanophilous globules, and globose to subglobose, yellowish to yellow basidiospores with irregularly arranged conical spines measuring 7–8 × 6.8–7.7 µm. Phylogenetic analyses using the internal transcribed spacer regions (ITS), the large subunit of the nuclear ribosomal RNA gene (nLSU), and the translation elongation factor 1-α gene (tef1-α) provided high support for L. terrestris as a new species in the family Stephanosporaceae. A full description, illustrations, and phylogenetic analysis results of the new species are provided here. A key to Lindtneria is also provided.